2008
DOI: 10.1080/02652030701714382
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element determination in acid-digested soy protein formulations by inductively coupled plasma–optical emission spectrometry

Abstract: The concentrations of major (Ca, K, Mg, Na and P) and trace elements (Al, Cu and Fe) in soy protein formulations sold in Bahia (Brazil) were determined by inductively coupled plasma-optical emission spectrometry (ICP-OES). Liquid and powdered soy protein formulation samples, both whole and light, were digested using a conventional heating program on a hot-plate. The powdered samples were prepared according to the label instructions for human consumption. A 5.0-ml aliquot of the soy protein emulsion was transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In general, higher levels of trace elements than our study were reported by Llorent-Martínez et al [ 25 ] in soy-based food acquired in Spain: Al (900–3000 µg/kg), As (2–4 µg/kg), Cd (1.5–5 µg/kg), Co (5–40 µg/kg), Cr (10–55 µg/kg), Cu (700–1300 µg/kg), Fe (4000–9400 µg/kg), Mn (1300–2400 µg/kg), Ni (100–500 µg/kg), Pb (2–8 µg/kg), Sb (<1.2–1.5 µg/kg), Sn (<1.5 µg/kg), and Zn (2100–3200 µg/kg). Boa Morte et al [ 26 ] also reported high levels of Al (0.98–2.02 mg/L), Cu (0.412–0.907 mg/L), and Fe (3.06–5.92 mg/L) in soy formulations from Bahia (Brazil), and Andrés et al [ 27 ] reported higher Zn levels in soy-based beverages containing fruit juice than in similar milk beverages.…”
Section: Resultsmentioning
confidence: 99%
“…In general, higher levels of trace elements than our study were reported by Llorent-Martínez et al [ 25 ] in soy-based food acquired in Spain: Al (900–3000 µg/kg), As (2–4 µg/kg), Cd (1.5–5 µg/kg), Co (5–40 µg/kg), Cr (10–55 µg/kg), Cu (700–1300 µg/kg), Fe (4000–9400 µg/kg), Mn (1300–2400 µg/kg), Ni (100–500 µg/kg), Pb (2–8 µg/kg), Sb (<1.2–1.5 µg/kg), Sn (<1.5 µg/kg), and Zn (2100–3200 µg/kg). Boa Morte et al [ 26 ] also reported high levels of Al (0.98–2.02 mg/L), Cu (0.412–0.907 mg/L), and Fe (3.06–5.92 mg/L) in soy formulations from Bahia (Brazil), and Andrés et al [ 27 ] reported higher Zn levels in soy-based beverages containing fruit juice than in similar milk beverages.…”
Section: Resultsmentioning
confidence: 99%